Real-time radiation dosimetry using P-doped silica optical fiber - Zubair, H.T.; Oresegun, A.; Rahman, A.K.M. Mizanur; Ung, Ngie Min; Mat Sharif, Khairul A.; Zulkifli, M.I.; Yassin, S.Z. Muhd; Maah, Mohd Jamil; Yusoff, Zulfadzli; Abdul-Rashid, Hairul Azhar; Bradley, David Andrew; Omar, Nasr Y.M. (Elsevier, 2019)
Radiation dosimetry applications related to radiotherapy have clear importance in determining the accurate and safe delivery of patient prescribed doses. Versatile yet robust, high spatial resolutions, wide dynamic range real-time forms of dosimetry are called for. Doped silica optical fibers of sub-mm spatial resolution exhibit useful radioluminescence (RL) properties when exposed to ionizing radiation. In this study, primary investigations have been carried out on phosphorus-doped silica optical-fiber. High-energy clinical X-ray beams (6 MV and 10 MV) were used to irradiate the optical fiber, RL response being recorded for six dose-rates (between 100 MU/min and 600 MU/min) delivered by a Varian 2100 C/D linear accelerator. The P-doped optical-fiber showed linear RL response, with minimal observable memory and afterglow and plateau effects. The results indicate the P-doped optical-fiber dosimeter to have strong potential for use in radiotherapy applications.